VFTS 243 as predicted by the BPASS fiducial models. Issue 3 (2nd February 2023) - Stevance, H F; Ghodla, S; Richards, S; Eldridge, J J; Briel, M M; Tang, P
ABSTRACT: The recent discovery of an unambiguous quiescent black hole (BH) and main-sequence O star companion in VFTS 243 opens the door to new constraints on theoretical stellar evolution and population models looking to reproduce the progenitors of BH–BH binaries. Here, we show that the binary population and spectral synthesis fiducial models natively predict VFTS 243-like systems: We find that VFTS 243 likely originated from a binary system in an ∼15 d orbit with primary mass ranging from 40 to 50 $\mathrm{\, M}_\odot$ and secondary star with initial mass of 24–25 $\mathrm{\, M}_\odot$ . Additionally, we find that the death of the primary star must have resulted in a low-energy explosion E < 10 50 erg. With a uniform prior, we find that the kick velocity of the newborn BH was ≤10 $\, \text{km s}^{-1}$ . The very low eccentricity reported for VFTS 243 and the subsequent conclusion by the authors that the supernova kick must have been very small are in line with the peak in the posterior distribution between 0 and 5 $\, \text{km s}^{-1}$ found from our numerical simulations performed with a uniform prior. Finally, the reduced Hobbs kick distribution commonly used in BH population synthesis is strongly disfavoured.